Utilization of iodized salt in Halahalaya Hamlet, Kanreapia Village, Gowa Regency - Syarfaini, Syarfaini; Surahmawati, Surahmawati; Adha, Andi Syamsiah; Nurfadilla, Nurfadilla; Harfayani, Nabila; Thamrin, Muhammad Alflirian (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Salt is a dietary supplement and source of electrolytes for the human body. Salt contains iodine. Iodine is a trace mineral that must be present in the body to form thyroid hormones and is beneficial for the body's metabolism. Iodine deficiency leads to goiter disease at various stages, slows growth in children and adults, as well as lowers labour productivity. The purpose of this service activity is to find out the use of iodized salt in Halahalaya Hamlet, Kanreapia Village. This type of service is an observational activity with a population consisting of heads of households in 92 households in Halahalaya Village. Data on the use of iodized salt were collected through interviews and direct observation using questionnaires. The results of the service showed that out of 92 households, 87 households (94.6%) used packaged salt labelled iodine, 5 households (5.4%) did not use packaged salt labelled iodine, iodine test results of 12 households were white (13.0%). ), light purple iodine test results in 20 households (21.7%), dark purple iodine test results in 60 households (65.2%). The conclusion of the service is that the availability of iodized salt in Halahalaya Hamlet, Kanreapia Village is sufficient, but there is still a lack of community understanding of the use of good iodized salt, therefore cross-disciplinary cooperation is needed to a growing community knowledge.